2019
DOI: 10.5539/ijms.v11n4p113
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Governance on the Sustainability and Continuity of Family Businesses in Botswana

Abstract: Academic discussion on corporate governance and its related issues are clearly visible in any country with active capital markets. This suggests that good governance is a crucial factor for ensuring economic development. Of concern is the lack of continuity after the first generation of ownership and control. However, few studies can be found relating to smaller family businesses. With the aim of contributing to this knowledge gap, this study aimed at identifying the impact of family governance on the sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This can be explained by the fact that these enterprises have a simple governance structure with unified ownership and management. Moreover, the majority of family SMEs are still young and belonging to the first generation and therefore the need for family involvement in the business is less recognized (Nordvisqt et al ., 2014; Tadu and Chiguvi, 2019). The small size of the effect of governance on the sustainable longevity of family businesses is explained by the fact that Tunisian SMEs have a monistic leadership structure, hence the need for governance structures is less recognized (Hammouda, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This can be explained by the fact that these enterprises have a simple governance structure with unified ownership and management. Moreover, the majority of family SMEs are still young and belonging to the first generation and therefore the need for family involvement in the business is less recognized (Nordvisqt et al ., 2014; Tadu and Chiguvi, 2019). The small size of the effect of governance on the sustainable longevity of family businesses is explained by the fact that Tunisian SMEs have a monistic leadership structure, hence the need for governance structures is less recognized (Hammouda, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…, 2011; Memili et al ., 2017). Previous studies showed that there is a need for good family governance structure to promote the survival of family SMEs (Tadu and Chiguvi, 2019; Al Rawaf and Alfalih, 2023). Our findings are relevant for both Tunisian practitioners and policy-makers to improve the governance practices of family SMEs in order to enhance their sustainable longevity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations